Anteseden Terhadap Perilaku Pembelian Impulsif : Studi Pada Pelanggan Retail Fashion di Kota Banjarmasin - Nurcahyo, Rianto; Rosyada, Shofia (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2023)
Shopping centres is one of the places for customers to shop for various products, one of which is fashion products. Very often customers shop spontaneously and without prior planning which is referred to as impulse buying. This research was conducted to see and understand how impulse purchases in the consumer decision process based on previous studies. The consumptive behaviour of consumers shopping will have an impact on sellers who provide products in the form of goods or services in meeting the needs and desires of consumers, so that the role of the seller must be responsive and quick in managing his business so that consumers continue to shop at his shop. Meanwhile, consumers tend to have many choices in shopping in fulfilling their needs at a store. The success of marketers in being able to sell products to consumers so that consumers feel satisfied and make repeat purchases is a successful marketing strategy with a long process not a coincidence. This study aims to determine the effect of Visual Merchandising, Shopping Lifestyle, Sales Promotion, and Celebrity Endorsement on impulse buying behaviour. For the number of 160 respondents in the Banjarmasin area, Kalimantan with the data collection technique used is Quantitative using Regression data analysis. The results of this study state that Visual Merchandising, Shopping Lifestyle, Sales Promotion, and Celebrity Endorsement have a significant and positive influence on impulse buying behaviour. The results of the linear regression test on the celebrity endorsement variable on impulse buying behaviour, it is known that the significance value obtained is 0.000 which means less than 0.05 so, it can be concluded that the celebrity endorsement variable has an effect on the impulse buying behaviour variable.